Pemanfaatan Artificial Intelligence Dalam Akuntansi: Kajian Literatur Review - Ilma Amelia; Yovanna Nabila Azzahra; Abda Abda; Zul Azmi (Akuntansi, 2024)
Artificial Intelligence is a system created with advanced technology or a computer system that can understand, and imitate the intellectual abilities of people in various ways. The implementation of artificial intelligence (AI) accounting systems within the financial industry has bestowed accountants with substantial advantages. Gaining a comprehensive comprehension of the application of artificial intelligence in accounting is the objective of this research.The method used in this research is Structured Literature Review (SLR), where several articles published from 2012 to 2023 will be analyzed systematically. The literature was categorized according to relevant concepts and grouped as non-aligned themes to convey additional issues regarding the Utilization of Artificial Intelligence in Accounting. The anticipated outcome of this research endeavor is the provision of enhanced comprehension regarding the implementation of synthetic intelligence in the field of accounting, alongside an illumination of the obstacles that an organization may encounter while embracing this technology. with an enhanced comprehension of the practical implementations of synthetic intelligence, companies can develop better strategies and make more efficient decisions in managing their financial information.